The Influence of Organizational Culture and Organizational Commitment to Employee Work Discipline at the Bandung City Transportation Service - Ruli Mochammad Chaerudin; Riza Rizkiah (Sainteks: Jurnal Sain dan Teknik, 2023)
This study aims to determine whether the variable (X) organizational culture and organizational commitment affect the variable (Y) employee discipline. The data collection method was carried out using descriptive and verification methods through questionnaires distributed to employees of the Bandung City Transportation Office. Samples were taken as many as 40 respondents using Purposive Sampling. The data obtained were then processed using SPSS Version 22 and analyzed using multiple linear regression tools. Based on the research results that have been conducted by researchers, the Ttest test shows that organizational culture has an effect on employee work discipline with a low relationship level of 9.50%, organizational commitment has a positive and significant effect on employee work discipline by 84.10% and the R square test together shows that organizational culture and organizational commitment jointly have a positive and significant effect on employee work discipline of 85.70% while the remaining 14.30% are influenced by other parties not examined.